R Graphs cookbook : over 70 recipes for building and customizing publication-quality visualizations of powerful and stunning R graphs - Abedin, Jaynal (Quick answers to common problems, 2014)
Targeted at those with an existing familiarity with R programming, this practical guide will appeal directly to programmers interested in learning effective data visualization techniques with R and a wide-range of its associated libraries.